Penggunaan Akta Konsen Roya Akibat Sertifikat Hak Tanggungan Yang Hilang Pada Kantor Pertanahan Kabupaten Asahan - Fakhri Bahira Ibtihaj Lubis; Ahmad Fauzi; Ruslan Ruslan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the authority of notaries and Land Deed Making Officials (PPAT) in making a concession agreement deed due to a lost mortgage certificate, analyzing the stages and processes in registering a concession agreement deed due to a lost mortgage certificate at the Asahan Regency Land Office and assessing the position law and the use of a concession agreement deed due to a lost mortgage certificate at the Asahan Regency Land Office. This study uses a qualitative descriptive method with a case approach and a statutory approach. The results of the study indicate that the Royal Consent Deed was made with a notarial deed. Although the APHT, which is the "base" of making mortgage certificates, is a PPAT deed, the consent deed remains the authority of a notary, not a PPAT. The registration process and completeness of the documents related to the Roya application using the Roya Consensus deed are the same as the general Roya service, as regulated in the Regulation of the Minister of Agrarian Spatial Planning/Head of BPN Number 3 of 1997 and Regulation of the Minister of Agrarian Spatial Planning/Head of BPN Number 1 of 2010. Deed roya permit made by a notary, its position is only as a substitute for a mortgage certificate lost in the roya process, not for execution, so that its position cannot be equated with a mortgage certificate which has executorial power because it is not regulated by law..